DESIGN AND EVALUATION OF NIFEDIPINE FLOATING MATRIX TABLETS - Rohit Jaimini; Mayank Bansal (Journal of Biomedical and Pharmaceutical Research, 2020)
Floating drug delivery systems are retained in the stomach and are useful for drugs that are poorly soluble or unstable in intestinal fluid. Floating drug delivery system have a bulk density less than that of gastric fluids and so remain buoyant in the stomach without affecting the gastric emptying rate for a prolong period of time. Research work emphasized on design and evaluates nifedipine floating matrix tablets in which polymers i.e. hydroxyprophyl methyl cellulose (HPMC K100M, K4, and K15) was used. About 15-35 % of HPMC can be used as a polymer in the extended release formulations. So, here the polymer was used in the range of 16-36 %. Sodium bicarbonate (40%) is used as a gas generating agent. It can be used in the range of 25-50 %. The granules are prepared by wet granulation method. The prepared granules were evaluated for the bulk density, tapped density, bulkiness, angle of repose, compressibility index and hausner ratio. The values indicate good flow property. The compressed tablets were evaluated for hardness, uniformity of weight, friability, drug content, buoyancy lag time and duration of buoyancy. All the readings are within the prescribed limits. There was no interaction between the drug, polymer and excipients it was found out by IR studies. The in vitro drug release data indicate that the release of the drug depends upon the proportion of polymer present in the formulation. As the polymer ratio increases the release rate of the drug is prolonged. Keywords: Floating tablet, HPMC K100M, nifedipine, HPMC K4